2014
DOI: 10.9790/1959-03140108
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Effectiveness of Educating Program for Upgrading Nurses’ Knowledge Regarding Polycystic Ovaries Syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is the most common endocrine disease of women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…This clearly suggests that structured education programme has improved the knowledge among the study participants with respect to PCOS. Our findings are similar to those observed in other published literatures from Egypt and India [11], [13], [14]. Pre intervention knowledge scores of participants with family history:One hundred and forty-five (59.4%) study participants had a positive family history of PCOS and influence of this family history on pre intervention knowledge scores was analyzed using independent t-test.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This clearly suggests that structured education programme has improved the knowledge among the study participants with respect to PCOS. Our findings are similar to those observed in other published literatures from Egypt and India [11], [13], [14]. Pre intervention knowledge scores of participants with family history:One hundred and forty-five (59.4%) study participants had a positive family history of PCOS and influence of this family history on pre intervention knowledge scores was analyzed using independent t-test.…”
Section: Resultssupporting
confidence: 78%
“…There were 50 participants and a statistically significant difference in pre and post education scores were observed among the participants. The study concluded that the continuous education and training on PCOS is essential in order to update the knowledge of participants that helps them to contribute for early detection and prevention of complications of PCOS that is a common health issue among target population [11].…”
Section: Literature Surveymentioning
confidence: 99%
“…[30][31][32][33][34] In present study lack of awareness were found among majority of girls (78.4%), these findings are in agreement with other study of Sunanda et al, Sowmya et. al and Hadayat A et al [35][36][37] …”
Section: Discussionmentioning
confidence: 99%
“…After the educational sessions there was enhancement of knowledge score on PCOS. The findings of the present study showed that vast majority of studied nurses had never attended any formal training program about PCOS and the majority of them did not have any information regarding PCOS (Amasha & Heeba, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…Urgent solutions to address the issue on lack of knowledge on PCOS among nursing students were necessary as nurses played a pivotal role in educating and empowering women with PCOS (Amasha & Heeba, 2014). Amasha and Heeba (2014) had concluded that implementation of an education program was efficient in enhancing the level of knowledge of maternity nurses regarding PCOS. Therefore, nurses need to have a broad knowledge on PCOS.…”
Section: Discussionmentioning
confidence: 99%